A boa-fé objetiva nas relações jurídico-tributárias: os deveres do Poder Público - Doniak Junior, Jimir (2022)
The intention of this thesis is to study objective good faith in legal-tax relations, focusing mainly on the resulting duties imposed on the State. Therefore, we seek to conceptualize objective good faith, identify its legal nature, verify whether it would be applicable to legal-tax relations and, then, discuss how it acts in these relations and the resulting duties imposed on the State. The theme is of great theoretical and practical relevance: in today's complex world, the fulfillment of the duty to act in accordance with the parameters arising from objective good faith will be positive for the conflicting relationship between individuals/taxpayers and the State/Tax Administration. The hypothesis which we seek to demonstrate is that objective good faith has the legal nature of a general legal principle, being applicable to legal-tax relations and generating several and relevant duties to the State. In our study, we analyzed the positive law: the law statements contained in the Federal Constitution, in the National Tax Code, in laws and in complementary law statements. However, not only them. The correct performance of objective good faith depends on the actually existing conditions. Therefore, we do not limit ourselves to scrutinizing the legal texts, but also seeking the realization of the principle in judicial precedents, in real cases that have raised a lot of debate in recent years and that can be illuminated by the principle of objective good faith. The proposal, therefore, was to analyze objective good faith in a movement of coming and going between norms and facts, having as a guide the value of good faith